Non-Hodgkin's Lymphoma Presenting as a Primary Endobronchial Tumor - A Case Report (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2013)
Non-Hodgkin’s lymphoma (NHL) involving the endobronchial tree is uncommon, and the initial  presentation of NHL as an endobronchial tumor is extremely rare. Several clinical reports have described  bronchial-associated lymphoid tissue (BALT) lymphoma as an endobronchial lesion. A 77 year old male hospitalized in another hospital for acute breathlessness and mechanically ventilated.  He was shifted to Delhi Heart And Lung Institute because of failed extubation after 3 days of mechanical  ventilation and reintubated .Past History of intubation was present 1 month back and diagnosed as  a case of acute bronchitis. On evaluation at another hospital, the patient was found to have normal  chest radiograph. Chest examination revealed findings consistent assisted ventilatory breath sounds  associated with bilateral ronchi. Blood investigations were within normal limit. Contrast enhanced  computed tomography of the chest revealed endoluminal soft tissue mass lesion at carina significantly  obliterating bilateral main bronchi.USG Whole Abdomen revealed mild hepatomegaly and left renal  cortical cyst measuring 4×5 cm and grade l BPH.Fibreoptic bronchoscopy revealed a globular smooth  mass causing near complete obstruction of left main bronchus. Histopathological examination of the  endobronchial biopsy showed tumor cells have a round or oval nucleus that appears vesicular because  of margination of chromatin at the nuclear membrane, but large multilobed or cleaved nuclei predominate  in some cases . Immunohistochemical staining was positive for LCA, CD20, and CD79a and negative for  CD3, CD5, CD30, NSE, CK, Ki67, Chromogranin and Synaptophysin. While in the hospital, the patient  was managed with mechanical ventilation and symptomatic treatment. FOB and rigid Bronchoscope,  debulking of tumour growths was done using electrocautery snare. Patient was continued on overnight  mechanical ventilation and extubated after one day. Post extubation, patient remained alright without any  respiratory distress and discharged in stable condition. Latter on patient followed in Rajiv Gandhi Cancer  Hospital. He underwent PET scan of whole body, which revealed normal study. Patient was managed  with chemotherapeutic agents and he is still alive after 3 years of management without any symptoms. NHL rarely presents as an endobronchial growth and only histopathology can differentiate it from other  benign and malignant endobronchial masses. SAARC Journal of Tuberculosis, Lung Diseases & HIV/AIDS; 2012; IX(2) 37-40 DOI: http://dx.doi.org/10.3126/saarctb.v9i2.7978